The Role of Ai in Transforming Smes: Opportunities and Challenges - Gunturu , Srinivasa Rao (International Journal of Membrane Science and Technology, 2024)
Artificial Intelligence (AI) systems assist in enhancing data analysis with meaningful insights and promote real-time decision construction that implements blockchain technology in data security. This factor guides SMEs in managing big data by usage of predictive analysis and algorithms in reducing operational complexity in the USA. There are 33.2 million SMEs in the US and contribute 50% of the overall GDP in this country as per the 2023 report [1]. The application of AI and automation technology leads to improved work distribution and enhanced overall performance in handling the SME’s services. This factor encouraged operational facilities to use the real-time tracking system and promote the level of the smart manufacturing process. The primary research used 101 participants to conduct a survey on SME employees for the transformation of SMEs with AI in analyzing opportunities and challenges. This analysis reflects that most of the employees felt encouraged to adopt AI and blockchain in expanding the overall productivity of USA SMEs.